A falência da caracterização ocidental do “Ser”: o resgate ancestral do “Ser Biológico” para a justa proteção do meio ambiente - Pugliesi , Erica; Bagatini Marotti, Ana Cristina; Previde, Renato ((Des)troços: revista de pensamento radical, 2025)
Agamben uses the expression “Biological Life” to summarize the passivity of being in the loss of Rights. The text studies the fact that society returns to “Biological Being”, which would not have the passivity feared by Agamben, but would belong to a community, as in the tribe, and would prevent the arbitrary actions of those in power, protected by the system of corporeal/spiritual unity. The objectives are: to demonstrate the existence of a system that benefits those in power; to prove that corporeal/spiritual oneness favors unrest; to demonstrate the ancestral search for the “Biological Being” in order to change the way of life. Methodologically, the research adopts a qualitative approach, based on documentary analysis and bibliographic review, focusing on academic works, legislation and case studies. The results indicate that the original peoples who live in belonging to the environment, generate the protection of the biome they inhabit and maximize the principle of human rights as the modern being has never managed, which concludes that this ancestry of “Biological Life” should be sought as a disruptive means, as a turning point for the protection of the environment, but also as modern thinking in exchange for the archaic uniqueness indicated above, regenerating natural systems, integrating development and social justice.